Should Employers Invest in Employability? Examining Employability as a Mediator in the HRM – Commitment Relationship - Akkermans, Jos; Tims, Maria; Beijer, Susanne; De Cuyper, Nele (Frontiers in Psychology, 2019)
This study investigates the relationship between perceived investments in Human Resource (HR) practices and workplace commitment, from the perspective of social exchange theory. An innovative feature is that we introduce perceived employability as a potential mediator, thus bringing in a career perspective: our argument is that perceived investments in HR practices promote feelings of employability, which then create workplace commitment. Based on a 6-week follow-up sample (N=437) and a 1-year follow-up sample (N=127), the results of structural equation modeling analyses mostly provided support for our hypotheses. Participation and communication practices were linked to commitment via employability (in both samples), and training and development only in the short term (6-week sample). Performance feedback and reward practices, however, were unrelated to commitment via employability. Overall, our findings show that employees bring in career considerations, employability concerns in particular, in the exchange with their employer. In addition, we contribute to filling the HRM ‘black box’ by showing that employability might be an explanatory mechanism in the HR practices – outcome relationship.